The improvement of pressurized metered-dose inhaler and spacers for treating respiratory diseases - Abd Rahman, Muhammad Faqhrurrazi (2022)
The burden of respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD) is constantly increasing. The symptoms can be alleviated using a pressurized metered-dose inhaler (pMDI). However, poor inhalation technique incorporation with a high initial velocity of pMDI may compromise treatment efficacy. This problem can be tackled by optimizing the pMDI actuator nozzle and using a spacer. Thus, this research aims to improve drug deposition in the lower respiratory tract using an optimized pMDI actuator nozzle and spacers. This study employed computational fluid dynamic (CFD) to predict particle tracking, particle deposition, and spray plume characteristics. Three designs of actuator nozzle (Design A, Design B, and Design C), two designs of disposable spacers (AeroCup Design D and AeroCup Design E), and two designs of the valved-holding chamber (VHC) (AerospaAcer Design F and AerospaAcer Design G) had been studied. The selected designs were fabricated using a three-dimensional (3D) printer. Lastly, the simulation results were validated with particle imaging velocimetry (PIV). Based on these results, actuator nozzle Design C was selected due to the highest injection particle with a maximum velocity magnitude of 35.67m/s. Moreover, actuator nozzle Design C improved the drug deposition in the lower respiratory tract to 21.80% compared to the commercial pMDI (16.90%). AeroCup Design D shows outstanding performance by trapping the highest injection particle and reducing the particle velocity to the air velocity. The particle deposition in the lower respiratory tract improved up to 54.7%. Lastly, AerospaAcer Design G shows a promising result by trapping the highest injection particles and reducing the particles' velocity to the air velocity. AerospaAcer Design G further improved the particle deposition in the lower respiratory tract up to 69.8%. Overall, the spray plume analysis of the actuator nozzle in pMDI, disposable spacer, and VHC showed a similar trend with a percentage error below 5%.